Classification of global behavior of a system of rational difference equations. (November 2018) - Matsunaga, Hideaki; Suzuki, Rina
Abstract: This paper deals with a system of rational difference equations x n + 1 = a y n + b c y n + d, y n + 1 = a x n + b c x n + d, n = 0, 1, 2, …, where a, b, c, d are real numbers with c ≠ 0 and a d − b c ≠ 0 . We establish a representation formula of solutions of the system and classify global behavior of solutions when no initial values belong to the forbidden set of the system.